2018
DOI: 10.1021/jacs.8b03767
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Pd(II)-Catalyzed Intramolecular Oxidative 6-endoAminoacetoxylation of Unactivated Alkenes

Abstract: A novel asymmetric 6-endo aminoacetoxylation of unactivated alkenes by palladium catalysis, which yields chiral β-acetoxylated piperidines with excellent chemo-, regio- and enantioselectivities under very mild reaction conditions, has been established herein by employing a new designed pyridine-oxazoline (Pyox) ligand. Importantly, introducing a sterically bulky group into the C-6 position of Pyox is crucial to enhance the reactivity of the aminoacetoxylation of alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…This result indicated that the sterically hindered 1‐naphthyl group retarded the second arylation under these conditions. Compared to the synthetic routes [4e–g] described in the Introduction involving 4–6 steps, this work provides an efficient method to synthesize bulky and enantioenriched ( S )‐pyridine‐oxazoline ligands in two steps starting from commercially available 6‐methyl‐2‐pyridinecarbonitrile and β‐amino alcohols [9] with reasonable to good yields. Although it was viewed as unlikely that the stereocenter in the pyridine oxazoline‐based ligands would be racemized by the base under these mild conditions, we viewed it as prudent to verify this hypothesis using chiral phase SFC (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that the sterically hindered 1‐naphthyl group retarded the second arylation under these conditions. Compared to the synthetic routes [4e–g] described in the Introduction involving 4–6 steps, this work provides an efficient method to synthesize bulky and enantioenriched ( S )‐pyridine‐oxazoline ligands in two steps starting from commercially available 6‐methyl‐2‐pyridinecarbonitrile and β‐amino alcohols [9] with reasonable to good yields. Although it was viewed as unlikely that the stereocenter in the pyridine oxazoline‐based ligands would be racemized by the base under these mild conditions, we viewed it as prudent to verify this hypothesis using chiral phase SFC (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…For example, bulky N , N ’‐bidentate ligands derived from 2,2′‐bipyridine and enantioenriched pyridine‐oxazolines have been used in metal‐catalyzed carbon dioxide reduction [4c,d] (Scheme 1a), enantioselective alkene difunctionalization reactions [4e–g,i] (Scheme 1b) and enantioselective electrochemical homocoupling reactions [4h] (Scheme 1c) with enhanced catalytic activity. In these reactions, the bulky ligands were implemented to prevent undesirable catalyst dimerization [4c,5] or to increase the metal center's electrophilicity toward binding olefin substrates [4f] . One drawback to these new catalytic processes is that existing methods for the synthesis of these bulky ligands involved laborious multistep procedures and only offered limited structural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that introducing a sterically bulky group into a chiral Pyox ligand at the C6‐position could significantly increase the catalytic reactivity of L*Pd II complex toward amination of alkenes and induce excellent enantioselectivity as well, which prompted us to survey the possibility of the catalytic asymmetric trifluoromethoxylation reaction. As an initial investigation, we focused on the reaction of 1 a in the presence of the privileged chiral Pyox ligand L1 under our Pd II /SelectFluor ® /AgOCF 3 systems.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous studies on the catalytic asymmetric aminoacetoxylation reaction, chiral 6‐substituted pyridine‐oxazoline (Pyox) ligands were tested for the reaction of 1 a . Unfortunately, low enantioselectivity and poor reactivity were observed when using the ligands L1 and L2 (Table , entries 1–2).…”
Section: Methodsmentioning
confidence: 99%